Genetic characterisation of Cryptosporidium parvum in dairy cattle and calves during the early stages of a calving season - Paul M. Bartley; Johan H. Standar; Frank Katzer (Current Research in Parasitology and Vector-Borne Diseases, 2024)
Cryptosporidium parvum is a causative agent of cryptosporidiosis, an infectious gastroenteritis in neonatal ruminants, which can be fatal in severe cases. The aim of this study was to determine the prevalence of infections in dairy cattle/calves during the early stages of a calving season and the species/genotypes of the Cryptosporidium present. Faecal samples collected from pre- and post-partum dams (n = 224) as well as calves from age ∼1 day onwards (n = 312) were examined. Oocysts were concentrated, DNA extracted and tested by Cryptosporidium 18S rRNA gene PCR and sequencing, while genotypes of C. parvum were determined by gp60 and VNTR analysis. Results showed that 31.3% and 30.4% of pre- and post-partum dams tested positive for Cryptosporidium, respectively. In the adults, C. parvum (n = 52), C. bovis (n = 4) and C. andersoni (n = 19) were identified, while in the calves 248 out of 312 (79.5%) were PCR-positive for C. parvum. The proportion of positive calf samples was significantly higher (P < 0.0001) than the proportion of positive adult cattle during the first seven weeks of the calving season. In adult cattle, three distinct gp60 genotypes were identified, a predominant genotype IIaA15G2R1 (n = 36) and genotypes IIaA15R1 (n = 2) and IIaA14G2R1 (n = 1). In the calves, only genotype IIaA15G2R1 was detected (n = 125). Although C. parvum was observed in adult cattle two weeks after the start of the calving season, the predominant genotypes were not detected until Week 4 in both adults and calves, meaning it is still unclear whether adult cattle are the initial source of C. parvum infections on the farm. Historically calves on this dairy farm demonstrated the IIaA19G2R1 genotype, which, has now clearly been replaced with the IIaA15G2R1 genotype that is now found in both adults and calves. During the study season, significantly higher levels of neonatal calf mortality were observed compared to the seasons before (P = 0.046) and after (P = 0.0002). This study has shown comparable levels of C. parvum infection in both pre- and post-partum dams but higher levels of infection in neonatal calves.